Inter-individual differences in how presentation modality affects verbal learning performance in children aged 5 to 16. Issue 7 (2nd October 2016) - Meijs, Celeste; Hurks, Petra P. M.; Wassenberg, Renske; Feron, Frans J. M.; Jolles, Jelle
Abstract : This study examines inter-individual differences in how presentation modality affects verbal learning performance. Children aged 5 to 16 performed a verbal learning test within one of three presentation modalities: pictorial, auditory, or textual. The results indicated that a beneficial effect of pictures exists over auditory and textual presentation modalities and that this effect increases with age. However, this effect is only found if the information to be learned is presented once (or at most twice) and only in children above the age of 7. The results may be explained in terms of single or dual coding of information in which the phonological loop is involved. Development of the (sub)vocal rehearsal system in the phonological loop is believed to be a gradual process that begins developing around the age of 7. The developmental trajectories are similar for boys and girls. Additionally, auditory information and textual information both seemed to be processed in a similar manner, namely without labeling or recoding, leading to single coding. In contrast, pictures are assumed to be processed by the dual coding of both the visual information and a (verbal) labeling of the pictures.